CURRENT ISSUES OF PENSION REFORM IN THE RUSSIAN FEDERATION - Anna Savtsova; Victor Koibaev (Вестник Северо-Кавказского федерального университета)
Demographic aspects influencing the state of the pension system are analyzed in artirle, the main indicators of pension provision, the number of pensioners registered in the system of the Pension Fund of the Russian Federation in the context of various categories are considered, their dynamics is given, the reasons for the formed situation are estimated, the problems in the sphere ofpension provision are revealed, the authors analyze foreign experience, the assessment of the consequences of the decision-making by the Government of the Russian Federation in matters of optimization of the financial mechanism of the pension system is given, suggests some directions for the solution ofproblems.